Understanding medical education : evidence, theory and practice - Swanwick, Tim (Wiley-Blackwell, 2010)
"Understanding Medical Education was launched as a series of monographs in September 2006, and was the brainchild of Association of Medical Education's then Chief Executive, Frank Smith. It has provided an outstanding success, selling over 40 000 copies worldwide. The series was designed to meet the needs of all newcomers to medical education including those studying at certificate, diploma or masters level and contributors have included experts from all walks of medical education from across the world. These popular monographs have now been collected into a single core textbook, providing a comprehensive guide to the theoretical and academic bases to modern medical education practice"--Provided by publisher